Assessment of the Library Collection of the Central Luzon State University Library: Basis of the Collection Development Program - Lasig, Camia Abergos; Madia, Roselyn M.; Reyes, Nuelah SJ.; Morales, Vanessa B.; Garabiles, Richie N. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2024)
Objective – The collection assessment project of the University Library is significant in determining whether the quantity of the collection meets the regulatory standard of the Commission on Higher Education (CHED) for academic libraries. This study specifically sought to find the level of library collection compliance in terms of major subject courses, to determine the curricular programs that are compliant with the standard or have a high rate of compliance, and to identify the curricular programs that should be prioritized in acquiring additional book titles.Methods – The assessment was conducted using an action research model of iterative reflection and improvement. It follows the four steps for carrying out the research: plan, act, observe, and reflect, as proposed by Davidoff and Van den Berg (1990). Furthermore, we employed CHED Memorandum Order (CMO) No. 22, Series of 2021, Section 4 (b.4-5) to analyze the collection's compliance based on its quantity. The data was presented using a table and percentage.Results – There are 32 undergraduate curricular programs offered at Central Luzon State University, which include 1,055 major subject courses. More than half of major subject courses (57.3%) on various curricular programs are non-compliant with CHED criteria, including 17.63% of major subject courses with zero titles copyrighted within the last five years. Findings also reveal that only 6 (18.75%) of the total programs were able to reach above 70% compliance with CHED standards, and there are 23 curricular programs with title gaps of 50% or higher that need to be prioritized in the acquisition of book titles.Conclusion – The library collection assessment technique is crucial for identifying gaps in the collection and determining areas where additional resources may be required. As the findings indicate that more than half of the major subject courses do not meet the requirements set by CHED, the librarians have been investigating ways to acquire additional academic sources to fill this gap. However, their current efforts are not yet enough to meet the requirements. A long-term plan for gradually building up the collection has been devised.